Microdeletions of ELP4 Are Associated with Language Impairment, Autism Spectrum Disorder, and Mental Retardation. Issue 9 (30th June 2015) - Addis, Laura; Ahn, Joo Wook; Dobson, Richard; Dixit, Abhishek; Ogilvie, Caroline M; Pinto, Dalila; Vaags, Andrea K; Coon, Hilary; Chaste, Pauline; Wilson, Scott; Parr, Jeremy R; Andrieux, Joris; et al.
<x xml:space="preserve">Abstract</x> We have identified a significant excess (p = 7.5 × 10−3) of small deletions (shown as red lines on the figure) at the PAX6‐ELP4 locus, 11p13, in three cohorts of patients with neurodevelopmental disorders. The deletions predispose to a range of phenotypes including autism spectrum disorder, language impairment, mental retardation and epilepsy, and likely disrupt the functions of the Elongator protein complex and/or the transcription factor PAX6.